Gender-Based Violence-Supportive Cognitions in Adolescent Girls and Boys: The Function of Violence Exposure and Victimization. Issue 3 (February 2021) - Debowska, Agata; Boduszek, Daniel; Jones, Adele D.; Willmott, Dominic; Sherretts, Nicole
Violence against women and girls is widespread in the Caribbean, which may be due to heightened acceptance of such acts in this specific social context. In spite of this, studies investigating attitudes toward violence and their correlates among participants drawn from the region are missing. To address this void in the literature, we examined associations between violence exposure and victimization and two gender-based violence-related cognitions (attitudes toward male physical domestic violence and social norms regarding physical violence against girls) as well as general beliefs about violence using structural equation modeling. Participants were a sample of adolescent girls ( n = 661; M age = 13.15) and boys ( n = 639; M age = 13.22) from two Eastern Caribbean countries, Barbados and Grenada, recruited from 10 primary schools, nine secondary schools, and two youth offender centers. In considering that girls and boys were previously demonstrated to differ in their experiences as well as tolerance of violence, structural models were specified and tested separately for the two sexes. Results indicated that violence victimization was positively strongly associated with attitudes toward male physical domestic violence and social norms regarding physical violence against girls among boys. Increased violence victimization among girls, in turn, correlated with increased acceptance of social norms regarding physical violence against girls, but this relationship was weak. Violence exposure did not have any significant associations with any of the attitudinal variables included in the study. We discuss the importance of these findings for the development of appropriate gender-based violence prevention strategies for youths from the Eastern Caribbean.